2015
DOI: 10.7206/mba.ce.2084-3356.146
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Policy Making and the Implementation of Regulatory Impact Assessment in Croatia

Abstract: Purpose: This study is dealing with the application of evidence-based policy-making in Croatian public administration and the general role of applied policy analysis in the Croatian system of governance.Methodology: This development is illustrated by the peculiarities of introducing regulatory impact assessment (RIA) tools in Croatian public administrative structures. Findings:The author is pointing out various limitations in the usage of policy analysis tools in formulating, implementing and evaluating public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
4
0
2
Order By: Relevance
“…Santoro et al [ 41 ] found the same in their study of 17 Eastern European countries. Petak [ 42 ], reporting on the Croatian policy process, mirrored our findings on shortcomings in coordinating government actors and monitoring implementation. Gollust et al [ 43 ] reported that mutual distrust is also key in the United States, while Innvaer et al [ 44 ] noted the same in a systematic review including studies mostly from high-income countries.…”
Section: Discussionsupporting
confidence: 76%
“…Santoro et al [ 41 ] found the same in their study of 17 Eastern European countries. Petak [ 42 ], reporting on the Croatian policy process, mirrored our findings on shortcomings in coordinating government actors and monitoring implementation. Gollust et al [ 43 ] reported that mutual distrust is also key in the United States, while Innvaer et al [ 44 ] noted the same in a systematic review including studies mostly from high-income countries.…”
Section: Discussionsupporting
confidence: 76%
“…At the EU level, better regulation policies ensure that "decision-making is open and transparent; citizens and stakeholders can contribute throughout the policy and law-making process; EU actions are based on evidence and understanding of the impacts; regulatory burdens on businesses, citizens or public administrations are kept to a minimum. " 5 Th e smart regulation is based on the question "how to achieve policy goals and better results through legislation with minimum disruption" (Petak 2015).…”
Section: Reform Content and Backgroundmentioning
confidence: 99%
“…All of the above represents a great challenge in creating a procedure for performance‐based policy evaluation and policy making. One of the latest policy‐planning approaches is evidence‐based policy making, which is widely applied in public administration (Petak, ). There are several types of policy/legislation impact assessment procedures that have been used in the past two decades, such as regulatory impact assessment (RIA), sustainability impact assessment (SIA), and simply impact assessment (IA).…”
Section: Literature Reviewmentioning
confidence: 99%